Lemierre Syndrome involving Schaalia (Formerly Actinomyces) odontolyticus due to injection drug use into the neck - Roohali A. Sukhavasi; Nina J. Gao; Christopher J. Smith; Sarah A. Schmalzle (IDCases)
Lemierre Syndrome, septic thrombophlebitis of the internal jugular vein following oropharyngeal infection, is classically caused by Fusobacterium necrophorum and associated with septic emboli. We present a case of Lemierre Syndrome involving Schaalia odontolyticus (formerly Actinomyces) in the setting of injection drug use. A 46-year-old man presented with right neck swelling and abscess with S. odontolyticus as the primary bacterium isolated from the abscess culture, which was introduced to the site when the patient had licked his needle and injected illicit drugs into his neck. The patient did not develop septic emboli, had sterile blood cultures, and was treated with surgical drainage and 2 weeks of oral linezolid without anticoagulation, with presumed cure. S. odontolyticus is a fastidious commensal oral bacterium involved in the formation of dental plaque, but has also been associated with severe extra-oropharyngeal manifestations. S. odontolyticus infections been increasingly reported in the literature, likely related to the advent of advanced identification technology like matrix-assisted laser desorption ionization-time of flight mass spectrometry, which can more easily identify fastidious organisms.